VALUE CHAIN MANAGEMENT STRATEGIES AND OPERATIONAL EFFICIENCY IN NIGERIAN LOGISTICS ORGANISATIONS - Nwibere, Barinedum Michael; Needorn, Richard Sorle (Web of Journals Publishing, 2024)
The research investigated the correlation between value chain management strategies and operational efficiency. A sample of 115 managers and supervisors from ten logistics firms in Nigeria was purposefully selected for the study. Employing a quasi-experimental research design, a cross-sectional survey method was used to gather data. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS) Version 25, utilising structural equation modelling (SEM) through the AMOS package. The results revealed a positive and significant connection between value chain management strategies and operational efficiency within Nigerian logistics firms. Specifically, the study observed positive and significant relationships between timely service delivery and operational efficiency indicators (such as cost-minimization efforts, sales volume, and market share). Similarly, a positive and significant correlation was identified between delivery channel stability and operational efficiency indicators. Furthermore, a positive and significant association was found between service quality and operational efficiency measures within Nigerian logistics firms. In light of these findings, the study concludes that value chain management strategies significantly enhance the operational efficiency of logistics firms in Nigeria. Notably, it emphasises the roles of timely service delivery, delivery channel stability, and service quality in augmenting cost-minimization efforts, sales volume, and market share in these firms. The study also deliberated on the theoretical and managerial implications of these findings.
Keywords: Cost-Minimization Efforts, Delivery Channel Stability, Market Share, Operational Efficiency, Sales Volume, Scientific Package for Social Sciences, Service Quality, Strategic Choice Theory, Structural Equation Modelling, Timely Delivery, Transaction Cost Economy, Value Chain Management Strategies.